A Review Article on Proniosome: As A Drug Carrier - Sachan, Anupam Kr.; Kumar, Sunil; Dwivedi, Tapasya (Asian Journal of Pharmaceutical Research and Development, 2021)
A drug carrier is any substrate used in the process of drug delivery. The basic component of the drug delivery system is an appropriate drug carrier that sets out to improve the selectivity, effectiveness, and safety of drug administration. So, based on their biocompatible, biodegradable, and non-immunogenic structure, Proniosomes are promising drug carriers that are non-ionic surfactant-based multilamellar or unilamellar vesicle are now widely used as an alternative to the liposome. On the basis of structure, they are similar to liposomes in having bilayer but having chemical differences in monomer units which make Proniosomes stable. They can entrap both hydrophilic and lipophilic drugs of using either in an aqueous layer or in the vesicular membrane. Proniosomal carriers are suitable for the transdermal delivery of numerous pharmacological agents, including antioxidant, anticancer, anti-inflammatory, antimicrobial, and antibacterial molecules.